PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK KEMAMPUAN BERBICARA SISWA PADA MATERI DONGENG KELAS I SDN 141 PEKANBARU - Dina Alfarida; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the validity of animated video media in class I fairy tale subjects Indonesian SDN 141 Pekanbaru. This research uses development research with the ADDIE development model. This research uses three stages, namely (1) the analysis stage, namely teacher needs analysis, curriculum analysis and media analysis, (2) the design stage, namely the design of making learning media as needed, (3) the development stage is the validity test stage. Data sources are obtained from primary data, namely teachers and validators, while secondary data is obtained from books, journals, articles and references from the internet related to development research. Data collected through interviews, questionnaires and documentation techniques. Analyzed qualitatively and quantitatively. The results of this study showed that the assessment of the material aspect of animated video media obtained a percentage of 85,6% with very valid criteria and the media aspect of animated video media obtained a percentage of 91.25% with very valid criteria. Overall, the validity of animated video media obtained an average value of 88,4% so that this animated video media was very valid without revision.